When the heavens went on sale the misfits and geniuses racing to put space within reach - Vance, Ashlee 1977- (WH Allen, 2023)
"With the launch of the Falcon 1 rocket in 2008, Elon Musk's SpaceX became the first private company to build a low-cost rocket that could reach orbit. And that milestone carried major implications: Silicon Valley, not NASA, was suddenly cemented as the epicenter of the new Space Age. Start-ups and the wealthy investors behind them began to realize that the universe-ungoverned and infinite-was open for business. Welcome to the wild west of aerospace engineering. When the Heavens Went on Sale tells the remarkable, unfolding story of this frenzied intergalactic land grab. Through his trademark immersive reporting, Ashlee Vance follows four pioneering companies-Astra, Firefly, Planet Labs, and Rocket Lab-as they build new space systems and attempt to launch rockets into orbit.
Includes index
Keywords: Rockets (Aeronautics) / Research / Popular works; Space tourism; Outer space / Civilian use; Privatization; Rockets (Aeronautics) / Research; Outer space; TRANSPORTATION / General; Popular works